2008
DOI: 10.1063/1.2978362
|View full text |Cite
|
Sign up to set email alerts
|

The initial atomic layer deposition of HfO2∕Si(001) as followed in situ by synchrotron radiation photoelectron spectroscopy

Abstract: We have grown HfO2 on Si(001) by atomic layer deposition (ALD) using HfCl4 and H2O as precursors. The early stages of the ALD were investigated with high-resolution photoelectron spectroscopy and x-ray absorption spectroscopy. We observed the changes occurring in the Si2p, O1s, Hf4f, Hf4d, and Cl2p core level lines after each ALD cycle up to the complete formation of two layers of HfO2. From the analysis of those variations, we deduced the growth properties of HfO2. The first layer consists of a sparse and Cl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…[70][71][72] There are also reports of XAS as an in vacuo technique, where the sample can be transferred from the ALD chamber to an UHV system to allow for XAS. [36][37][38][39] To the best of our knowledge, the use of XAS as an in situ technique has been performed once on powderous supports in absorption mode 40 and once studying ALD growth on a planar support in fluorescence mode. 41 B. X-ray photoelectron spectroscopy XPS is a technique that allows the study of composition and chemical state of the elements in a material.…”
Section: A X-ray Absorption Spectroscopymentioning
confidence: 99%
“…[70][71][72] There are also reports of XAS as an in vacuo technique, where the sample can be transferred from the ALD chamber to an UHV system to allow for XAS. [36][37][38][39] To the best of our knowledge, the use of XAS as an in situ technique has been performed once on powderous supports in absorption mode 40 and once studying ALD growth on a planar support in fluorescence mode. 41 B. X-ray photoelectron spectroscopy XPS is a technique that allows the study of composition and chemical state of the elements in a material.…”
Section: A X-ray Absorption Spectroscopymentioning
confidence: 99%
“…To enable such synchrotron based experiments, a dedicated ALD setup is required that is preferably mobile so that it can be used at different beamline end stations (enabling different x-ray based characterization techniques), preferably at different synchrotron user facilities. In recent years, "in situ" setups have been developed at the National Synchrotron Light Source (NSLS I) at Brookhaven National Lab (by temporarily transforming a multi-purpose UHV chamber at beamline X21 into an ALD reactor), 10,24 at the Pohang Light Source (PLS), 14 at the Advanced Photon Source (APS) at Argonne National Laboratory, 21 at Stanford Synchrotron Radiation Lightsource (SSRL), 20 and at SOLEIL, 19,22 while "in vacuo" setups have been developed at BESSY II 25,26 and at SSRL, 27,28 mainly targeting XPS.…”
Section: Introductionmentioning
confidence: 99%
“…11 The HfO 2 deposition has therefore catalyzed the oxidation at the interface between the silicon substrate and the chemically stable ultra thin thermally grown oxide. This increase in interfacial oxide thickness with high-k deposition has previously been observed in a number of studies [12][13][14] and has been identified as forming in the initial phase of deposition. The likely cause of this interfacial oxide growth at room temperature is the enhanced dissociation of O 2 into atomic oxygen in the presence of hafnium atoms due to the metal atom catalytic effect.…”
mentioning
confidence: 63%